From Waste to Resource: Evaluating the Impact of Biosolid-Derived Biochar on Agriculture and the Environment - Hailey Mcintyre; Simeng Li (Biomass)
The escalating production of biosolids from wastewater treatment plants presents significant environmental and health challenges due to the presence of pathogens, trace organic pollutants, and heavy metals. Transforming biosolids into biochar through pyrolysis offers a sustainable solution, enhancing soil fertility and mitigating greenhouse gas emissions. This review critically evaluates the pyrolysis processes (slow, fast, and flash) for biosolid conversion and examines the impact of biosolid-derived biochar on soil nutrient retention, crop productivity, and greenhouse gas emissions. Findings from various studies demonstrate that BDB can significantly reduce emissions of N2O, CH4, and CO2 while improving soil health. However, challenges such as standardizing production methods, addressing heavy metal content, and ensuring economic feasibility must be overcome. Future research should focus on optimizing pyrolysis conditions, developing regulatory frameworks, and conducting comprehensive economic analyses to support the large-scale implementation of BDB in sustainable agriculture.